Development of Digital Library at SDN Bontoa, Tamalanrea District, Makassar City - Putrawan, Muh. Rizah; Hartoto, Hartoto; Atjo, Syamsuryani Eka Putri; Mubarak, M. Fadli (International Journal of Education, Vocational and Social Science, 2025)
Schools already have references in printed books, but teachers need more references in digital form so that they can be integrated in class and/or in students' independent learning as a learning resource. The purpose of this study is to (1) Develop a Digital Library at SDN Bontoa, Tamalanrea District, Makassar City (2) Measure the Feasibility and Validity of the Digital Library at SDN Bontoa, Tamalanrea District, Makassar City. The approach used in this study is development research using the ADDIE model which consists of 5 stages, namely (Analysis, Design, Development, Implementation and Evaluation). The data analysis technique uses a Likert scale, final data conversion and percentage of answers. The results of this study indicate that the assessments given by media experts and material experts for this Digital Library are in the feasible/valid category so that they can be recommended as a learning resource. This is proven by the existence of expert validation instruments and material experts who are in the feasible/valid category. The digital library at SDN Bontoa, Tamalanrea District, Makassar City can be used as a reference in digital form so that it can be integrated in class and/or in students' independent learning as a learning resource